(untitled) (Bangladesh Rice Journal, 2021)
High input-intensive Boro rice cultivation needs substantial agricultural credit for the resource-poor Bangladeshi farmers. An investigation was conducted at Fulbaria upazila of Mymensingh district to assess loan attainment cost from Bangladesh Krishi Bank (BKB) and its utilization pattern; evaluate the effects of credit on Boro cultivation, and identify the major drivers of the agricultural credit programme. For the study, 140 farmers were divided into two groups: those who took a loan from BKB and those who did not. Results revealed that the borrowers had to pay Tk 10.23 for getting a hundred taka loan from BKB most of which was an unofficial cost. More than half of the obtained loan was used for Boro cultivation whereas 21% was used for family consumption and the rest (25%) was used for other purposes such as reimbursement of the previous loan from formal and informal sources, wedding and other income-generating activities including petty business. BKB credit borrowers obtained more benefits through Boro cultivation than non-borrowers. The major strengths of the BKB’s agricultural credit programme were well-established infrastructure, experienced manpower, country-wide network, and lower interest rate. Whereas complex and lengthy institutional procedures, the inevitability of collateral and poor institutional capacity were being revealed as the weaknesses of the programme. Prevalence of brokers or corrupt officials and political influence were identified as the major constraints for the loan acquirement. More advanced research is recommended, with an emphasis on agricultural credit programmes, to ensure their effectiveness. Bangladesh Rice J. 24 (1): 85-95, 2020